2015
DOI: 10.1371/journal.pone.0124863
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in a Permanently Cold and Alkaline Environment in Greenland

Abstract: The submarine ikaite columns located in the Ikka Fjord in Southern Greenland represent a unique, permanently cold (less than 6°C) and alkaline (above pH 10) environment and are home to a microbial community adapted to these extreme conditions. The bacterial and archaeal community inhabiting the ikaite columns and surrounding fjord was characterised by high-throughput pyrosequencing of 16S rRNA genes. Analysis of the ikaite community structure revealed the presence of a diverse bacterial community, both in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 83 publications
4
27
0
1
Order By: Relevance
“…Recent amplicon sequencing studies of the microbial diversity in the apex of ikaite columns showed the presence of a phototrophic surface‐associated community dominated by cyanobacteria (Glaring et al ., ; Trampe et al ., ). The very first characterization of the in situ ikaite microenvironment was recently reported by Trampe et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent amplicon sequencing studies of the microbial diversity in the apex of ikaite columns showed the presence of a phototrophic surface‐associated community dominated by cyanobacteria (Glaring et al ., ; Trampe et al ., ). The very first characterization of the in situ ikaite microenvironment was recently reported by Trampe et al .…”
Section: Introductionmentioning
confidence: 97%
“…The Ikka fjord in SW Greenland harbours a unique assemblage of underwater tufa columns composed of the hexahydrated carbonate mineral ikaite (Pauly, 1963;Buchardt et al, 1997), which forms a porous matrix harbouring a diverse assemblage of microbes (Stougaard et al, 2002;Vester et al, 2013;Glaring et al, 2015). Hundreds of columns are situated in the innermost part of the Ikka fjord in South-western Greenland (Seaman and Buchardt, 2006), while ikaite column formation or larger solid ikaite assemblages have not been documented from other locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The columns are formed by precipitation of calcium carbonate from the mixture of seawater and alkaline spring water, and the interior of the columns is permanently cold (less than 6°C) and alkaline (above pH 10) (Buchardt et al, 1997;Hansen et al, 2011). It has previously been demonstrated that the columns are home to a diverse bacterial community adapted to these conditions (Schmidt et al, 2006;Vester et al, 2013) and a potential source of novel enzymes (Schmidt and Stougaard, 2010;Vester et al, 2014Vester et al, , 2015Glaring et al, 2015). Similar extreme conditions can be found in a series of alkaline ponds with pH values above 10 located in the McMurdo Dry Valley region, Antarctica (Jungblut et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on metagenomic data, the abundance of Bacteroidetes is about 10-20 % in alkaline lake sediments (Xiong et al, 2012;Zaitseva et al, 2014;Glaring et al, 2015). Bacteroidetes has an important role in the marine carbon cycle, involved in the degradation of high-molecular-mass compounds such as cellulose, agar and chitin (Cottrell & Kirchman, 2000;Kirchman, 2002;Abell & Bowman, 2005).…”
mentioning
confidence: 99%